2011
DOI: 10.1007/s11548-011-0545-9
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution variable-dose imaging in digital radiography: quality and dose reduction with a fluoroscopic flat-panel detector

Abstract: The phantom testing images and simulation results demonstrate that diagnostic quality SR-radiographic images of skeletal extremities can be synthesized using a flat-panel detector system designed primarily for angiography. SR-images obtained with substantially reduced radiation dose are feasible, and this technology may improve digital radiography for pediatric, neonatal radiography, or mammography applications. Further testing is needed to validate super-resolution techniques in other body regions and for dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…However, its usefulness in joints with an unphysiological joint anatomy, such as it is the case in osteoarthritis (presence of osteophytes), is limited. In a previous study, Berliner et al showed that flat-panel detector systems can produce high quality radiographic images at a substantially reduced radiation dose in comparison with conventional computed radiography [15]. Future studies will have to evaluate the role of flat-detector guided imaging for routine interventions in terms of reduction of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, its usefulness in joints with an unphysiological joint anatomy, such as it is the case in osteoarthritis (presence of osteophytes), is limited. In a previous study, Berliner et al showed that flat-panel detector systems can produce high quality radiographic images at a substantially reduced radiation dose in comparison with conventional computed radiography [15]. Future studies will have to evaluate the role of flat-detector guided imaging for routine interventions in terms of reduction of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%